Fotoliza WWA w roztworach wodnych = Photolysis of PAHs in water solutions - Turek, Agnieszka; Włodarczyk-Makuła, Maria (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
In natural environment photolysis takes place in the surface layer of surface waters and soil. The yield of photolysis depends on the irradiation intensity, pH and temperature. In the waters there is a natural organic matter, which components can both inhibit and facilitate the process of oxidation of PAHs. Aromatic hydrocarbons under the influence of light and oxygen are easily photochemical reactions to form derivatives, which identification is not exactly recognized.
Keywords: WWA; HPLC; fotodegradacja; pH; PAHs; photodegradation